Efektivitas Media Mentimeter Pada Pemahaman Materi Bahasa Arab Era Pandemi Covid-19 - Desi Rahmania Zulfa; Nurul Huda (IAIN Madura, 2021)
This research is motivated by the lack of motivation to learn, the difficulty of students in understanding the material, and the monotonous and boring learning methods. Therefore, innovative learning methods and media are needed so that the learning process becomes more enjoyable. Then the media can be used as a solution to these problems. The purpose of this study was to determine the effectiveness of the mentimeter media in understanding student material. This research is quantitative research with experimental type. The design of this research was the Pre-test Post-test Control Group Design which was carried out at MTsN 9 Bantul by using a random sampling technique. Based on statistical calculations that have been carried out in the experimental class and control class, the significance value is 0.000. Because the sig value 0.000 <0.05, it can be concluded that Ha is accepted. Thus it can be said that there is a difference in the understanding of the Arabic language material for classes using mentimeter media with classes using conventional media.